Deciphering Cryptic Population Structure in Western Sandhill Crane Subspecies (Antigone canadensis) of the Pacific Flyway - Ruth Joy; Krista Roessingh; Kathleen Meszaros; Allyson Miscampbell; Carol Ritland; Matt Hayes; Gary Ivey; Mike Petrula; Jeffrey B. Joy (Ecology and Evolution)
ABSTRACT Population segregation catalyses genetic differentiation and can lead to speciation. Population genetic structure is also critically important for population management, especially in species characterised by small, isolated populations. Sandhill Crane (Antigone canadensis) populations of the Pacific Flyway are made up of breeding populations nesting west of the Rocky Mountains, and isolated by intermediate mountain ranges. Current management policy in British Columbia treats all Sandhill Cranes as a single population, whereas in the western United States, subpopulations are subject to population‐specific management. Here, we analyse microsatellite markers, mitochondrial DNA sequences, and mitochondrial haplogroups derived from 203 individual Sandhill Cranes to elucidate the population genetic structure of cranes migrating along the Pacific Flyway to summer breeding habitat on the North and Central Coast of British Columbia and Southeast Alaska. STRUCTURE, AMOVA, FST, DAPC, and phylogenetic analyses reveal that geographically separated crane populations along the west coast of North America show substantial genetic differentiation in the Pacific Flyway. These findings are consistent with behavioural and ecological evidence—divergent diets, flyways, and breeding habitats. We conclude that the relatively small coastal Sandhill Crane populations deserve special management consideration to safeguard their genetic diversity and adaptations, and to mitigate deleterious impacts of current and future climate change scenarios.